1936
DOI: 10.1084/jem.64.6.897
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diet Upon the Regeneration of Serum Protein

Abstract: In the evaluation of dietary proteins for their influence upon the regeneration of serum protein, it should be taken into consideration that the protein which is ingested must serve in two ways, namely, (a) in meeting the minimal requirement for nitrogen equilibrium of the entire organism and (b) in the formation of new serum protein. Inasmuch as proteins differ with respect to the amounts required for (a), it is obvious that preliminary determinations of the quantities needed for this purpose should be conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

1938
1938
1955
1955

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…If the basal diet is inadequate no certain baseline can be established. This opinion relative to reserve stores differs from that held by others (8).…”
contrasting
confidence: 85%
See 2 more Smart Citations
“…If the basal diet is inadequate no certain baseline can be established. This opinion relative to reserve stores differs from that held by others (8).…”
contrasting
confidence: 85%
“…Interesting experiments have been reported by Melnick and Cowgill (8,9) which are obviously related to the problems involved in the experiments tabulated in this paper. A detailed discussion of the differences between their work and ours would not seem appropriate in this place.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar data by different technics have been obtained by Weech (2) and by Melnick, Cowgill, and Burack (3), although the latter group concluded that the differences between serum, casein, and lactalbumin were not significant. It thus appears that plasma proteins may be considered to be of high biological value as measured by these technics.…”
supporting
confidence: 78%
“…As a result of the work of others (7, 11 to 16), it is recognized that ingested proteins differ widely in their ability to regenerate plasma albumin. Our work has been entirely with protein hydroly- When the assay values for the same hydrolysate given by mouth and by vein are compared, we can again elicit no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%